Case report: solitary fibrous tumor of pleura - Magalhães Paiva, Débora; Fernandes Vieira, Amanda; Durães Rocha, Emanuelly; Cardoso Murta Botelho, Matheus; Silva Lima, Thaisa; Araújo Gomes Cabral , Sabrina; Aparecida Alves Barbosa, Romana; Bernadina Miranda Soares, Príscila (Revista Unimontes Científica, 2020)
ESTUDO DE CASO: TUMOR FIBROSO SOLITÁRIO DA PLEURA Case report: solitary fibrous tumor of pleura Abstract: The present article is an analysis and a study on the Solitary Fibrous Tumor of the Pleura (SFTP), which is a neoplasm of origin in the pluripotent cells of the fibrous mesenchyme. The neoplasia is not exclusive to the pleura, it also affects extra thoracic tissues such as muscles, soft parts, pelvis and abdomen. It is a rare tumor type pathology, affecting approximately 2.8 patients in 100,000, corresponding to 5% of all pleural neoplasms. It presents more than 80% of tumors characterized as benign. It has unknown etiology and is not associated with genetic factors or life habits. Biopsy and immunohistochemical analysis are essential for the definitive diagnosis of the disease, as well as imaging test. The treatment of choice is complete surgical excision. The study also analyzes the case of a 46-year-old male patient who was admitted to the Montes Claros hospital in January 2018. Therefore, the study addresses all the disease characteristics that have developed in this patient, as well as the clinical, diagnostic and therapeutic discussions of the Solitary Fibrous Tumor. Resumo: O presente artigo faz uma análise e estudo de caso acerca do Tumor Fibroso Solitário de Pleura que é uma neoplasia de origem nas células pluripotentes do mesênquima fibroso. A neoplasia não é exclusiva da pleura, acomete também tecidos extratorácicos como músculos, partes moles, pelve e abdômen. É uma patologia de tipo de tumor raro, afetando aproximadamente 2, 8 pacientes em 100.000, correspondendo a 5% de todas as neoplasias pleurais. Apresenta mais de 80% dos tumores caracterizados como benignos. Possui etiologia desconhecida, não sendo associado a fatores genéticos, nem a hábitos de vida. A biópsia e a análise imuno-histoquímica são essenciais para o diagnóstico definitivo da patologia, assim como os exames de imagem. O tratamento de escolha é a excisão cirúrgica completa. O estudo faz ainda uma análise do caso de um paciente do sexo masculino com idade de 46 anos, que deu entrada no hospital de Montes Claros em janeiro de 2018. O estudo aborda, portanto, as características da doença, que desenvolveram neste paciente, bem como as discussões clínicas, diagnósticas e terapêuticas do Tumor Fibroso Solitário.